2017
DOI: 10.1292/jvms.16-0516
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence and genotyping of <i>Chlamydia</i> spp. in wild birds from South Korea

Abstract: Wild birds are reservoirs for Chlamydia spp. Of the total 225 samples from wild birds during January to September 2016 in Korea, 4 (1.8%) and 2 (0.9%) showed positive for Chlamydia psittaci and Chlamydia gallinacea, respectively. Phylogenetic analyses and comparisons of sequence identities for outer-membrane protein A (ompA) revealed that Korean C. psittaci fall into three previously known genotypes; genotype E, 1V and 6N, whereas the Korean C. gallinacea were classified as new variants of C. gallinacea. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
0
21
0
4
Order By: Relevance
“…The mean Cq value in the Chlamydiaceae qPCR in these birds was 29.1 with values ranging from 14.1–38.3, thus suggesting that the bacteria in samples with low Cq values may have been actively replicating, and the positive result was not only due to residual bacteria from infected prey. Further, ompA genotyping revealed that one common buzzard harbored C. psittaci genotype 1V, a C. psittaci / C. abortus intermediate that has a host preference for corvids [ 10 , 34 , 39 ]. As all samples were found negative for C. buteonis using species-specific qPCR, it remains unknown whether this recently described chlamydial species does occur in raptors in Switzerland.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean Cq value in the Chlamydiaceae qPCR in these birds was 29.1 with values ranging from 14.1–38.3, thus suggesting that the bacteria in samples with low Cq values may have been actively replicating, and the positive result was not only due to residual bacteria from infected prey. Further, ompA genotyping revealed that one common buzzard harbored C. psittaci genotype 1V, a C. psittaci / C. abortus intermediate that has a host preference for corvids [ 10 , 34 , 39 ]. As all samples were found negative for C. buteonis using species-specific qPCR, it remains unknown whether this recently described chlamydial species does occur in raptors in Switzerland.…”
Section: Discussionmentioning
confidence: 99%
“…Further, ompA genotyping revealed that one common buzzard harbored C. psittaci genotype 1V, a C. psittaci/C. abortus intermediate that has a host preference for corvids [10,34,39]. As all samples were found negative for C. buteonis using species-specific qPCR, it remains unknown whether this recently described chlamydial species does occur in raptors in Switzerland.…”
Section: Raptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 32 33 Genotype E, which was found in one fancy pigeon, infects a variety of avian species and is frequently found in pigeons worldwide. [34][35][36][37] Both genotypes are zoonotic, but human infection is mostly associated with genotype A causing a more severe course of disease. [38][39][40] Chlamydiaceae were not detected in any other bird order included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca, kesin olmayan 1V, YP84, R54, 6N, CPX0308, I gibi alt genotipleri de vardır. Serotiplerde konak özgüllüğü vardır 8 . Serotip A esas olarak psitasin kuşlarından, serotip B esas olarak güvercinlerden, serotip C çoğunlukla ördeklerden ve kazlardan, serotip D çoğunlukla hindilerden, serotip E ise çoğunlukla güvercinlerden ve diğer kuşlardan izole edilir.…”
Section: Introductionunclassified